Towards a typology of discourse-based approaches to language attitudes. (September 2017) - Rodgers, Elena
Abstract: This paper reviews discourse-based approaches to language attitudes in terms of their contributions to understanding the creation of socio-indexical meaning in metalinguistic discourse. It proposes a five-level typology of approaches which includes topic-oriented, linguistic, cognitive, interactional, and rhetorical analyses. The article discusses the ways in which different types of analyses expose various aspects of social-semiotic and meta-semiotic processes involved in constructions of sociolinguistic indexical relations in the local interactional and larger contextual frames. The paper argues in favor of integrated discourse-based approaches and illustrates the potential of a rhetorical approach to serve as a unifying framework for blending analytical levels. Highlights: Proposes a five-level typology of discourse-based approaches to language attitudes. Reviews topic-oriented, linguistic, cognitive, interactional, and rhetorical analyses. Discusses differences in analyses of social-semiotic and meta-semiotic processes. Argues for integrated multi-level discourse-based approaches to language attitudes. Illustrates a rhetorical approach as a unifying framework for integrating analyses.